HUBUNGAN KOMUNIKASI INTERNAL DENGAN KINERJA PEGAWAI PADA DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KAB. BENGKULU TENGAH - Hasana, Nurlaila; Anggriani, Ida; Prawitasari, Andriyani (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2016)
Communicating is importance for everyone inside organization. All members in the organization must use communications to perform tasks. The process of communication that occurs in the organization especially internal communication is an important factor in creating an effective organization with to improve employee performance. Internal communication is well established can strengthen relationships among employees and generate trust, confidence, openness, honesty, security support, satisfaction work. The purpose of this study is to determine the relationship of internal communication with the performance of employees at the Office of Revenue Management Finance and Regional Assets Bengkulu Tengah District. The method of analysis used is the validity and reliability test, rank spearman correlation, hypothesis test. The result of spearman rank correlation analysis obtained by spearman rank correlation value 0,96 is 0,800 - 1,000 interval, it means relationship between internal communication (X) with performance of officer of Revenue Service, Financial Management and Asset of Regency of Bengkulu Tengah is very strong and test value t obtained significant results where the significant value in the table is 0,000 and the value of t count 37.87> t table 1.99 means Ho is rejected and Ha accepted so it is proven that internal communication has a significant relationship with the performance of employees on the Office of Revenue, Financial Management and Assets Region of Bengkulu Tengah Regency.Keywords:Â  Internal Communication, Employee Performance